Measuring suffering. Issue 1 (March 2015) - Cunningham, Tim
<x xml:space="preserve">Abstract</x> Ever increasing humanitarian crises involve prolonged population displacement, a known trigger for chronic stress, which in turn highlights the need for chronic stress to be addressed more explicitly within humanitarian aid work. This calls for better tools to both assess chronic stress in these situations of extended displacement, as well as methods to evaluate the impact of psychosocial interventions in such settings. Noting these challenges, this paper proposes the use of hair cortisol concentration sampling to measure long-term suffering and stress. By including cortisol hair testing as a quantitative measure to complement existing measures of psychosocial programme surveillance, researchers may better understand the nature of chronic stress. Sampling any sort of biomarker, such as cortisol concentration in hair, raises ethical and logistical concerns, therefore this paper address these issues as well, maintaining that a 'do no harm' position should take priority over the decision to measure hair cortisol concentration. Furthermore, as there is also a paucity of evidence regarding the validity of hair cortisol testing on humans, further research will be required.